Associations between Family Maltreatment Perpetration and Latent Profiles of Personal and Family Strengths among Active-Duty Air Force Members - Jensen, Todd M. (Journal of family violence, 2022)
Although individual and family strengths have been found to impact family maltreatment risk, optimal approaches to their assessment are lacking. To substantiate the utility of holistically assessing multiple strengths among active-duty Air Force members (i.e., Airmen) who might be at risk of perpetrating family maltreatment, the current study aimed to identify latent patterns of personal and family strengths among Airmen and assess associations with family maltreatment perpetration. A representative a sample of 30,187 Airmen from the 2011 Air Force Community Assessment Survey was used to identify patterns across latent-factor scores representing unit leader support, informal support, family functioning, individual fitness, and personal resilience. Latent profile analysis was conducted to extract an optimal number of response patterns and estimate associations with family maltreatment perpetration. A five-profile solution was optimal, representing patterns marked by low (10%), below average (26%), mixed (16%), above average (36%), and high (12%) levels of personal and family strengths. Predicted probabilities of family maltreatment among families not identifying as stepfamilies were 39%, 21%, 14%, 10%, and 8% across low, below average, mixed, above average, and high patterns, respectively. Among stepfamilies (20% of sample), predicted probabilities were 49%, 29%, 21%, 15%, and 12%, respectively. Findings encourage a holistic assessment of personal and family strengths among Airmen. The Personal and Family Strengths Inventory, which was developed to gauge these strengths, can position practitioners well to engage Airmen in conversations around strengths and growth opportunities for the purposes of service planning aimed at preventing family maltreatment.